2015
DOI: 10.1097/qai.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Early HIV-1 Infection Is Associated With Reduced Frequencies of Cervical Th17 Cells

Abstract: These data support the model of initial CD4 T-cell depletion followed by overall T-cell influx in response to infection and concomitant increases in immune activation, inflammation, and regulatory markers. These data are among the earliest characterization of the cellular milieu in the female genital tract following male-to-female HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…HIV/SIV efficiently replicate in Th17 as demonstrated by studies by our group and others [40-48]. More specifically, mucosal Th17 cells represent major targets of HIV/SIV infection [49, 50] and subsequent rapid depletion [51-57]. Consistent with this paradigm, a very recent study identified CCR6 + RORgt + Th17 as the first cells to be infected upon vaginal SIV challenge [58].…”
Section: Introductionmentioning
confidence: 78%
“…HIV/SIV efficiently replicate in Th17 as demonstrated by studies by our group and others [40-48]. More specifically, mucosal Th17 cells represent major targets of HIV/SIV infection [49, 50] and subsequent rapid depletion [51-57]. Consistent with this paradigm, a very recent study identified CCR6 + RORgt + Th17 as the first cells to be infected upon vaginal SIV challenge [58].…”
Section: Introductionmentioning
confidence: 78%
“…10,51 Another group has also recently shown these to be optimal HIV target cells. 52 Furthermore, MIP-3a is increased in the cervix during early HIV infection, 53 and blockade of chemokines including MIP-3a by antiinflammatory glycerol monolaurate prevented nonhuman primates from acquiring Simian immunodeficiency virus infection. 11 However, it is worth noting that as we did not ascertain the cellular source of these protein factors, future experiments will be needed confirm that they originated from neutrophils vs. other immune cells of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complete understanding and the etiology of epithelial disruption during HIV infection remains unclear, it is known that these tight junctions are breached during HIV infection [6], which has been linked to many immunological influences [9**]. For example, homeostatic T cell subsets are lost very early in infection, including Th17 cells, which are crucial in responding to bacterial antigens [10*,11*]. Indeed, Th17 cells in HIV infection are thought to aid in maintainence of the epithelial barrier by amplifying signals of microbial translocation [12].…”
Section: Introductionmentioning
confidence: 99%